Análise da paisagem do município de Salto de Pirapora, SP como subsídio para planejamento ambiental - Pires, Valquíria Rodrigues de Oliveira (2016)
The disorderly process of land use and occupation in Salto de Pirapora city, resulting in an intense forest fragmentation, and the lack of research in the city, led the development of this work, organized into three chapters. With the main objective to determine areas of interest for conservation and thus provide support for Salto de Pirapora planning and environmental management. Chapter 1 describes the mapping of use and occupation of land, and was set 14 classes. The results indicated an agroforestry system matrix, with the following most representative classes in the territory: clean field representing 29.49% of the municipal area, followed by forestry class with 21.88%. The forest remnants represent 21.32% of the territory. It also describes the situation of the Protect Area of the city, that doesn’t have a decree regulating its functioning, showing an urgent need to expedite the process of its creation. Chapter 2 describes the Permanent Preservation Areas conflict, indicating that 17.16% of the city is occupied by PPA streams and springs. Of this percentage, 50.70% have vegetation and 41.94% lies in a situation of conflict, highlighting the importance of a recovery plan for the natural vegetation of these areas. Chapter 3 addresses the areas of interest for conservation selected by AHP. According to the results, 700 mapped fragments, 9 had priority Very High and 14 had High (3.29%), corresponding to 44.71% of the forest cover. Adding the fragments of Very Low and Low classes, was obtained 534 fragments (76.29%), corresponding to 32.94% of the vegetation cover. The AHP application in GIS environment for selecting conservation areas of interest was efficient in evaluating the distribution of the fragments in the landscape according to their priority, offering alternatives to assist the territorial planning and arrangement process of the city. And finally, it is concluded that the current scenario of forest cover in Salto de Pirapora city is worrisome due to the disorderly process of land use and occupation. It is hoped that these findings will contribute to the characterization of the territory and assist the decision of the planners regarding the development of conservation strategies and forest restoration programs, especially in Permanent Preservation Areas. Through multi-criteria analysis, areas of interest for conservation based on their ecological relevance can be prioritized, providing support for the process of planning and environmental management of the city and facilitates the targeting of conservation actions for the whole territory.